The Efforts of Bhabinkamtibmas Through the Door-To Door-System (DDS) Visit to Prevent the Crime of Motor Vehicle Theft in the Jurisdiction of The Boyolali Police - Calvin Ido (Advances in Police Science Research Journal, 2022)
Motor vehicle theft is a crime that can happen to all levels of society. The rise of theft incidents is a disturbance to the social security and order which is very troubling to vehicle owners. The police as the protectors of the community are obliged to maintain social security and order through the function of Community Development by carrying out door-to-door system visit, which are the efforts of the police in preventing the crime of motor vehicle theft and increasing public participation and awareness in maintaining social security and order. This study aims to describe the phenomenon of theft, describe the role of the door-to-door system counseling by Bhabinkamtibmas, identify the factors that influence the door-to-door system counseling, and examine relevant theories and concepts in preventing the crime of motor vehicle theft in the jurisdiction of the Boyolali Police. The theory used in this research is Role Theory and Management Theory. Furthermore, the concepts used in this study include the concept of crime prevention, the concept of Bhabinkamtibmas and the concept of motor vehicle theft. This research was conducted using a qualitative approach with field research methods through direct data collection from relevant agencies, interviews, literature studies combined with validation and triangulation technique. The results of the study found that the settlement of motor veficle theft cases in the jurisdiction of the Boyolali Police was still very low. So that the role of Bhabinkamtibmas through door-to-door system visit is expected to increase public awareness of the law, vigilance in situations prone to theft, and massively increase public participation in efforts to prevent motor vehicle theft. This study examines the application of management theory by applying POAC based on factual conditions which include information and intelligence regarding problems, rules and regulations related to activities, organizational resources and internal-external factors